Entrepreneurial Management Development of Tourism Potential to Enhance Community Economic Empowerment: Evidence from Mallenreng Beach, Indonesia - Asrul; Makmur; Rusdiana; Dini Ikayanti; Nur Amin; Mochamad Nurdin; Muh Amar; Muhlis Hajar Adiputra; Irmawati; Harianto; Mawar; Muhammad Lutfi; Amiruddin; Akriandi Amin; Mifta Fadhli As’ad (Masterpiece, 2026)
This study examines the development of entrepreneurial management in utilizing tourism potential as a strategy to enhance community economic empowerment, with empirical evidence from Mallenreng Beach, Panaikang Village, Sinjai Regency, Indonesia. Despite possessing significant coastal tourism potential, Mallenreng Beach has faced persistent challenges related to weak management practices, limited human resource capacity, inadequate tourism infrastructure, low marketing capability, and the absence of business legality among local micro, small, and medium enterprises (MSMEs). This research adopts a community-based empowerment approach implemented through the Program for Strengthening Student Organization Capacity (PPK ORMAWA) initiated by the Scientific Writing Student Activity Unit of Universitas Muhammadiyah Sinjai. The program employed participatory methods, including needs assessment, training, mentoring, and monitoring, focusing on tourism management, MSME business legality (Business Identification Number and Halal Certification), product branding and packaging, digital marketing, and village website management. The findings demonstrate a significant improvement in managerial capacity among tourism managers, increased formalization of MSMEs through legal certification, enhanced product attractiveness and marketing reach, and improved digital promotion of village tourism potential. These outcomes contributed to increased community participation, strengthened local economic activities, and improved institutional collaboration between stakeholders. This study contributes to the literature on entrepreneurial tourism management by providing practical evidence that integrated capacity-building interventions can effectively transform local tourism resources into sustainable drivers of community economic empowerment in rural coastal areas